Increase in HFC‐134a emissions in response to the success of the Montreal Protocol. Issue 22 (18th November 2015) - Fortems‐Cheiney, A.; Saunois, M.; Pison, I.; Chevallier, F.; Bousquet, P.; Cressot, C.; Montzka, S. A.; Fraser, P. J.; Vollmer, M. K.; Simmonds, P. G.; Young, D.; O'Doherty, S.; et al.
Abstract: The 1, 1, 1, 2‐tetrafluoroethane (HFC‐134a), an important alternative to CFC‐12 in accordance with the Montreal Protocol on Substances that Deplete the Ozone Layer, is a high global warming potential greenhouse gas. Here we evaluate variations in global and regional HFC‐134a emissions and emission trends, from 1995 to 2010, at a relatively high spatial and temporal (3.75° in longitude × 2.5° in latitude and 8 day) resolution, using surface HFC‐134a measurements. Our results show a progressive increase of global HFC‐134a emissions from 19 ± 2 Gg/yr in 1995 to 167 ± 5 Gg/yr in 2010, with both a slowdown in developed countries and a 20%/yr increase in China since 2005. A seasonal cycle is also seen since 2002, which becomes enhanced over time, with larger values during the boreal summer. Key Points: New estimation of HFC‐134a emissions from 1995 to 2010 Seasonal cycle seen since 2002 during the boreal summer Annual US budgets increasing after 2005, in disagreement with the EPA's estimates